Precursors of the spin glass transition in three dimensions. (22nd August 2019) - Baity-Jesi, Marco; Martín-Mayor, Víctor
Abstract: We study energy landscape and dynamics of the three-dimensional Heisenberg spin glass model in the paramagnetic phase, i.e. for temperature T larger than the critical temperature . The landscape is non-trivially related to the equilibrium states even in the high-temperature phase, and reveals an onset of non-trivial behavior at a temperature, which is also seen through the behavior of the thermoremanent magnetization. We also find a power-law growth of the relaxation times far from the spin-glass transition, indicating a dynamical crossover at a temperature, . The arising picture is reminiscent of the phenomenology of supercooled liquids, and poses questions on which mean-field models can describe qualitatively well the phenomenology in three dimensions. On the technical side, local energy minima are found with the Successive Overrelaxation algorithm, which reveals very efficient for energy minimization in this kind of models.